Yuriko Doi’s Teaching and Transmission of Noh and Kyōgen in San Francisco - Halebsky, Judith (Performance Matters, 2024)
Yuriko Doi founded the Theatre of Yugen in San Francisco and taught American students noh and kyōgen for more than thirty years. Noh theatre, in living practice in Japan for more than six hundred years, incorporates music, dance, acting, and singing. While noh is serious and sombre, kyōgen is a comedic form traditionally performed within or between noh plays. Starting in the late 1970s, Doi’s Theatre of Yugen performed new works inspired and informed by noh as well as kyōgen in English around the US and also in Japan. Noh training ideally begins in childhood as one-on-one study with a teacher and continues into adulthood. The transmission of noh is considered to be from body (teacher) to body (student) without verbal explication. To teach students in an ensemble theatre company in California, Doi adapted aspects of the transmission process as well as aspects of the form. Doi taught the exterior qualities of movement and vocal technique and, at the same time, tried to instill a sense of noh’s interior qualities, which include time, aesthetic intensity, and art practice as a life path. While teaching noh and kyōgen, Doi wants her students to draw from all of their training and influences. She explains that trying to hide other performance traditions held in the body, such as Western acting technique, will deflate the energy of a performance. She argues that if an actor can develop a complex sense of noh they can integrate it with all of the other knowledge structures in the body, which will lead to a masterful performance. Based on a series of interviews with Doi, the treatises of noh founder Zeami Motokiyo, and recent scholarship on noh, this essay examines the practice and transmission of noh and how the art is continued and revised through Doi’s work.